2020
DOI: 10.1090/proc/14984
|View full text |Cite
|
Sign up to set email alerts
|

Global smoothness for a 1D supercritical transport model with nonlocal velocity

Abstract: We are concerned with a nonlocal transport 1D-model with supercritical dissipation γ ∈ (0, 1) in which the velocity is coupled via the Hilbert transform, namely the so-called CCF model. This model arises as a lower dimensional model for the famous 2D dissipative quasigeostrophic equation and in connection with vortex-sheet problems. It is known that its solutions can blow up in finite time when γ ∈ (0, 1/2). On the other hand, as stated by Kiselev (2010), in the supercritical subrange γ ∈ [1/2, 1) it is an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In [29], Li and Rodrigo proved the finite-time blowup of smooth solutions to (1.3) in the supercritical case 0 < γ < 1 2 (see also [24,31,33] for different proofs for this blow-up result). Recently, for each smooth nonnegative initial data, Ferreira and Moitinho [18] obtained the existence of global classical solutions to (1.3) for γ ∈ (γ 1 , 1) with γ 1 depending on the H 3 2 -norm of the initial data. For the remaining case 1 2 ≤ γ < 1, whether smooth solutions to (1.3) may blow up in finite time is currently still open.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In [29], Li and Rodrigo proved the finite-time blowup of smooth solutions to (1.3) in the supercritical case 0 < γ < 1 2 (see also [24,31,33] for different proofs for this blow-up result). Recently, for each smooth nonnegative initial data, Ferreira and Moitinho [18] obtained the existence of global classical solutions to (1.3) for γ ∈ (γ 1 , 1) with γ 1 depending on the H 3 2 -norm of the initial data. For the remaining case 1 2 ≤ γ < 1, whether smooth solutions to (1.3) may blow up in finite time is currently still open.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Another proof of this dissipative singularity result via the telescopic sum argument is presented in [30]. Recently, in [19], Ferreira and Moitinho obtained the existence of global classical solutions to (1.6) with γ ∈ (γ 1 , 1), where γ 1 depends on some norm of the initial data. The question of global regularity vs finite time singularity for the dissipative CCF model (1.6) with 1 2 ≤ γ < 1 is open as well.…”
Section: R Nmentioning
confidence: 94%
“…in [4], where the authors concluded that the solutions would develop into gradient blow-up as κ = 0 and exist globally as κ > 0, α > 1. References [5,6] are recommended for some recent results on this transport equation.…”
Section: Introductionmentioning
confidence: 99%